Condensation modeling of the bolted joint structure with the effect of nonlinear dynamics - Lingfei, Kong; Heling, Jiang; Ghasemi, Amir H.; Yan, Li (Journal of sound and vibration, 2019)
In this paper, an order-reduction modeling method is proposed to capture the dynamic performance of a bolted joint structure. The model contains the influences of nonlinear contact force, damping and geometrical characteristics of connecting interface. The equations of motion of a bolted joint structure are divided into the linear characteristics and the nonlinear characteristics based on desired locations information. A new hybrid coordinate reduction (HCR) technique is introduced where the nonlinear characteristics within connecting interface are retained into the physical space while other linear modes are truncated. However, the error caused by truncating higher-order linear modes is compensated using a residual flexible matrix. The connecting interface of the bolted joint structure is condensed to a visual point via the coordinate transformation. The main advantage of this method is the reduced computational cost for solving the nonlinear dynamic equations. A series of experimental tests are performed to demonstrate the effectiveness of the proposed method. It is shown that the proposed method provides a more realistic tool for capturing the nonlinear dynamics and performance of a complex joint structure.